(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Objective: To determine the diagnostic accuracy of Doppler Ultrasonography in diagnosing endometrial carcinoma in females with post-menopausal bleeding taking histopathology as gold standard. Introduction: Postmenopausal bleeding (PMB) is one of the most common reasons in patients attending gynecological OPD. It is a frequent and alarming sign of endometrial cancer though the commonest cause is an atrophic endometrium. Women with PMB are categorized as those with spontaneous bleeding and those with bleeding whilst on Tamoxifen or HRT. All these patients should be investigated by TVS, hysteroscopy and D&C and accordingly should be managed. Methods: Study Design: Cross Sectional Study. Setting: Unit IV, Department of Obstetrics & Gynecology, Sir Ganga Ram Hospital, Lahore. Duration: Study was completed (01-07-13 to 30-12-14) Methodology: Total 250 cases were included in the study of age 50-70 years presented with clinically diagnosed postmenopausal bleeding (as per operational definition) undergoing hysterectomy. After approval from hospital ethical committee, 250 patients who fulfill the inclusion and exclusion criteria was enrolled in the study from OPD of Sir Ganga Ram Hospital, Lahore. Informed consent was obtained. All basic demographic information of each patient was obtained. Females were referred to radiology department for evaluation of endometrial thickness and RI value. If RI was to be <0.70, then patients were labeled as positive. This procedure was done by a single senior radiologist. Then patients were sent for hysterectomy, endometrial sampling was done and sample was sent to the histopathology laboratory of the hospital. Results: Mean age of all 250 women included in this study was 61.32±7.67 years. Mean endometrial thickness on Doppler ultrasonography was 8.81±4.36 mm. Mean resistive index on Doppler ultrasonography was 0.53±0.17. Sensitivity and specificity of Doppler ultrasound findings was 86.96% and 90.7% respectively. While positive predictive value, negative predictive value and overall diagnostic accuracy of Doppler ultrasound was 97.83%, 59.09% and 87.6% respectively. Conclusion: Results of this study showed good diagnostic results with the use of Doppler ultrasonography in the diagnosis of endometrial carcinoma in patients presenting with post-menopausal bleeding. Doppler ultrasonography is useful diagnostic tool with good sensitivity (86.97%), specificity (90.7%), PPV(97.83%) and NPV(59.09%). With its use patients can be prevented from unnecessary surgeries.